Lactobacillus rhamnosus GG increases cyclooxygenase‐2 expression and prostaglandin E2 secretion in colonic myofibroblasts via a MyD88‐dependent mechanism during homeostasis. (26th July 2018) - Uribe, Gabriela; Villéger, Romain; Bressollier, Philippe; Dillard, Rachel N.; Worthley, Daniel L.; Wang, Timothy C.; Powell, Don W.; Urdaci, Maria C.; Pinchuk, Irina V.
Abstract: Prostaglandin E2 (PGE2 ) plays a critical role in intestinal mucosal tolerance and barrier integrity. Cyclooxygenase‐2 (COX‐2)‐dependent PGE2 production involves mobilisation of arachidonic acid. Lactobacillus rhamnosus GG (LbGG) is one of the most widely used probiotics reported to colonise the colonic mucosa. LbGG contributes to the protection of the small intestine against radiation injury through the repositioning of mucosal COX‐2 expressing cells. However, it is unknown if LbGG modulates PGE2 production in the colonic mucosa under homeostasis and the major cellular elements involved in these processes. Colonic epithelial and CD90 + mesenchymal stromal cells, also known as (myo) fibroblasts (CMFs), are abundant innate immune cells in normal colonic mucosa able to produce PGE2 . Herein, we tested the hypothesis that under colonic mucosal homeostasis, LbGG modulates the eicosanoid pathway resulting in increased PGE2 production in both epithelial and stromal cells. Among the five tested human colonic epithelial cell lines, only exposure of Caco‐2 to LbGG for 24 hr led to the mobilisation of arachidonic acid with concomitant increase in the components within the leukotriene and COX‐2‐dependent PGE2 pathways. By contrast, CMFs isolated from the normal human colonic mucosa responded to LbGG with increased expression of COX‐2 and PGE2 in the prostaglandin pathway, but not 5‐LO in the leukotriene pathway. Oral gavage of C57BL/6 mice for 5 days with LbGG (5 × 10 8 Colony‐Forming Unit (CFU)/dose) increased COX‐2 expression in the colonic mucosa. The majority of cells upregulating COX‐2 protein expression were located in the colonic lamina propria and colocalised with α‐SMA + cells corresponding to the CMF phenotype. This process was myeloid differentiation factor‐88‐dependent, because silencing of myeloid differentiation factor‐88 expression in CMFs abrogated LbGG‐induced upregulation of COX‐2 in culture and in vivo. Taken together, our data suggest that LbGG increases release of COX‐2‐mediated PGE2, contributing to the maintenance of mucosal homeostasis in the colon and CMFs are among the major contributors to this process.